2016
DOI: 10.1590/0100-29452016512
|View full text |Cite
|
Sign up to set email alerts
|

Yellow Passion-Fruit Irrigated in Diferent Cropping Systems

Abstract: -With this study, the objective was to determine the most economic management of irrigation water applied at different levels in the culture of passion fruit grown in conventional system and in polyethylene bags. The experiment was conducted in the city of Remanso, state of Bahia, Brazil. The experimental set-up was a randomized block design in a factorial design 2 (conventional system, and polyethylene bags of 100 L) x 5 (irrigation levels: 100%, 80%, 60%, 40% and 20% an irrigation management at field capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Anthracnose is favored by high temperatures, high relative humidity, and periodic rainfall (GONÇALVES JÚNIOR et al, 2007). The optimum temperature ranges from 20 to 30 o C, the spore production is favored by temperatures around 27 o C, and disease is more severe in rainy conditions, between temperatures of 22 to 28 o C and high humidity (SERRA et al, 2008;RIBEIRO, 2016). The climatic conditions observed in this study were conducive to disease development, with high temperatures and high relative humidities.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…Anthracnose is favored by high temperatures, high relative humidity, and periodic rainfall (GONÇALVES JÚNIOR et al, 2007). The optimum temperature ranges from 20 to 30 o C, the spore production is favored by temperatures around 27 o C, and disease is more severe in rainy conditions, between temperatures of 22 to 28 o C and high humidity (SERRA et al, 2008;RIBEIRO, 2016). The climatic conditions observed in this study were conducive to disease development, with high temperatures and high relative humidities.…”
Section: Resultsmentioning
confidence: 66%
“…The vertical trellis system can result in higher productivity, but lower precocity than the overhead trellis system (NORBERTO et al, 2008). As for diseases intensity, changes in the plant canopy architecture can reduce the dispersion of pathogens, and create an unfavorable microclimate for disease development (ANDO et al, 2007;RIBEIRO, 2016). By tradition, the vertical trellis system is used in Southern Minas Gerais to grow grapevines.…”
Section: Introductionmentioning
confidence: 99%
“…The fresh matter of the aerial part superiority expresses the response of greater water content in the soil, and, therefore, the greater state of water energy in the leaves and turgor of the guard cells, with a positive reflection in biomass production by plants, in general (TAIZ et al, 2017), including sweet potato (DELZARI et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Almeida et al (2015) and Cui et al (2020) concluded that the water deficit inhibits crop photosynthesis, growth and production. This situation expresses the dependence of agricultural production systems on irrigation, in the semiarid world, and requires the adoption of water management strategies in order to obtain sustainable agricultural yields to guarantee food availability, given the growing global concern (SOUZA et al, 2016;DELZARI et al, 2017;EL-FOTOH et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation